Development of Solid Fuel Briquette from Coal Waste - NIK MAHAMED, NIK SAHIRA NAJIHA (IRC, 2016)
In order to satisfy the human needs, energy being the most essential, has left no option for researches to improve on other alternative fuels like fossil fuels energy etc. Therefore, an attempt is made by preparing solid fuel briquettes as an alternative source for energy application from highly available biomass coal waste, in Malaysia with massive amount of production yearly. Thus, problem can be solved by using coal waste which naturally exists with low bulk density and low moisture content will result in high durability characteristics of coal waste briquette. This study aims in identifying the characteristic of coal waste to be converted into a solid fuel briquette which promotes desirable quality with good fuel properties. Since there are two samples were carried out throughout the experiment, Sample 1 consists of coal waste, and Sample 2 consists of coal waste with a combination of Empty Fruit Bunch (EFB) that acts as a binder to strengthen the structure of the briquettes.